Acute macular neuroretinopathy: early receptor potential change suggests photoreceptor pathology. - Sieving, P A (1984)
The early receptor potential (ERP) was recorded in a patient with typical fundus findings of unilateral acute macular neuroretinopathy. These amplitudes were compared with those of a normal control population. The ERP amplitude of the affected eye measured 13 months after onset of visual impairment was significantly reduced (4.8 SD) compared with the normal fellow eye. A subsequent ERP measurement 7 months later (20 months after onset) showed the same amount of amplitude reduction, indicating that recovery had not occurred by this time. Since the ERP is generated during photolysis of visual pigment molecules and requires intact photoreceptor outer segment membranes to orient these molecules, our findings suggest that the outer segments are affected in at least some patients with this disorder. A retinal vascular aetiology for this disorder was rejected by studying a subject with a large retinal depression sign that occurred after a previous retinal vascular occlusion.